2017
DOI: 10.1080/00987913.2017.1385128
|View full text |Cite
|
Sign up to set email alerts
|

Delivering Open

Abstract: While providing access to an appropriate, available copy has long been an issue for libraries, open access (OA) content presents new challenges. In particular, the availability of OA publications outside of traditional content providers and the tendency for OA articles to appear in otherwise subscriptionaccess journals tends to thwart many existing library tools for delivering access. However, solutions are emerging-both for researchers who discover publications on the open web and who seek delivery via OA or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…7 Bulock notes that OA has "complicated" retrieval in that OA versions are often housed in various locations across the web, including institutional repositories (IRs), preprint servers, and personal websites. 8 There is no perfect search option or tool, although some have tried creating solutions, such as the Open Jericho project from Wayne State University, which is seeking to create an aggregator to search institutional repositories and eventually other sources as well. 9 However, this lack of a central search tool can lead to confusion among researchers.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Bulock notes that OA has "complicated" retrieval in that OA versions are often housed in various locations across the web, including institutional repositories (IRs), preprint servers, and personal websites. 8 There is no perfect search option or tool, although some have tried creating solutions, such as the Open Jericho project from Wayne State University, which is seeking to create an aggregator to search institutional repositories and eventually other sources as well. 9 However, this lack of a central search tool can lead to confusion among researchers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…9 However, this lack of a central search tool can lead to confusion among researchers. 10 Nicholas and colleagues found that their sample of early career scholars drawn from several countries relied heavily on Google and Google Scholar to find articles that interested them. 11 Many also turn to ResearchGate and other social media platforms and risk running afoul of copyright.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Instead of focusing on paid content, though, Unpaywall is delivering open access (OA) content. To accomplish this, Impactstory has "combined data from the Directory of Open Access Journals (DOAJ), Cross-Ref, a list of DOI prefixes, and more to create a large store of data on OA availability of scholarly publications"(Bulock, 2017). Unpaywall is available as an extension for both Firefox and Chrome.…”
mentioning
confidence: 99%